Eksplorasi, Identifikasi, dan Karakterisasi Nematoda Entomopatogen Pada Lahan Jagung dan Padi - Iqbal Erdiansyah; Anisa Nur Fauziah (Jurnal Ilmu Pertanian Indonesia, 2024)
Entomopathogenic nematodes (EPN) are potential nematodes as biological agents because they actively search for insect pests and are parasitic on their hosts. Two genera of EPN can be used as biological agents: Steinernema and Heterohabditis. It is necessary to explore local EPN on land suspected of having potential as a habitat for the nematodes. This study aimed to determine the genus and population of the EPN from corn and rice farms in Jember by identifying and characterizing them. The method used was the descriptive method. The EPN population was analyzed using the T-test. The results showed that the EPN from the corn and rice fields belonged to the Steinernema genus. EPN from the corn field isolate was characterized by a body length of 826,77 μm, body width of 47.14 μm, and tail length of 73.16 μm, while from the rice field, the isolate was characterized by a body length of 840.54 μm, body width of 37.70 μm, tail length 57.52 μm. EPN populations in maize and rice fields were not significantly different. Keywords: exploration, entomopathogenic nematodes, Steinernema